Designing and FOPID Controlling of the Wheeled-Legged Mobile Robot with Adjustable Height - Yigit, Tevfik; Celik, Hakan (Institute of Electrical and Electronics Engineers Inc., 2023)
In this study, a mobile robot with adjustable height has been designed and controlled. The mobile robot designed as wheeled-legged for improve mobility. Thus, it is possible to take and drop products to different height stations. Brushless DC (BLDC) motors has been used to joints and wheels. Thus, aimed to take advantages of the BLDC motor, which has fast torque response, high torque/volume ratio. Moth Swarm Algorithm (MSA) has been used to the obtaining Fractional-Order PID (FOPID) controller parameters. In addition, well-known and commonly used Integer-Order PID (IOPID) controller has been optimized in same conditions and it is used to comparison. When inspected the results, it has been seen that FOPID controlled BLDC motors has better performance than IOPID controlled BLDC motor. © 2023 IEEE.
10th International Conference on Signal Processing and Integrated Networks, SPIN 2023 -- 23 March 2023 through 24 March 2023 -- Noida -- 188530
Keywords: BLDC Motor; Fractional-Order Control; Mobile Robot; Wheeled-Legged Robot